CGL160-mediated recruitment of the coupling factor CF1 is required for efficient thylakoid ATP synthase assembly, photosynthesis, and chloroplast development in Arabidopsis. Issue 1 (17th October 2022) - Reiter, Bennet; Rosenhammer, Lea; Marino, Giada; Geimer, Stefan; Leister, Dario; Rühle, Thilo
Abstract: Chloroplast ATP synthases consist of a membrane-spanning coupling factor (CFO ) and a soluble coupling factor (CF1 ). It was previously demonstrated that CONSERVED ONLY IN THE GREEN LINEAGE160 (CGL160) promotes the formation of plant CFO and performs a similar function in the assembly of its c-ring to that of the distantly related bacterial Atp1/UncI protein. Here, we show that in Arabidopsis ( Arabidopsis thaliana ) the N-terminal portion of CGL160 (AtCGL160N) is required for late steps in CF1 -CFO assembly. In plants that lacked AtCGL160N, CF1 -CFO content, photosynthesis, and chloroplast development were impaired. Loss of AtCGL160N did not perturb c-ring formation, but led to a 10-fold increase in the numbers of stromal CF1 subcomplexes relative to that in the wild type. Co-immunoprecipitation and protein crosslinking assays revealed an association of AtCGL160 with CF1 subunits. Yeast two-hybrid assays localized the interaction to a stretch of AtCGL160N that binds to the DELSEED-containing CF1 -β subdomain. Since Atp1 of Synechocystis ( Synechocystis sp. PCC 6803) could functionally replace the membrane domain of AtCGL160 in Arabidopsis, we propose that CGL160 evolved from a cyanobacterial ancestor and acquired an additional function in the recruitment of a soluble CF1 subcomplex, which is critical for the modulation of CF1 -CFO activity and photosynthesis. Abstract : The green-lineage specific N-terminal domain of CGL160 recruits coupling factor 1 and its lack affects chloroplast development, photosynthesis and thylakoid ATP synthase assembly in Arabidopsis.